2019
DOI: 10.1038/s41598-019-38838-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of E. coli Inactivation by Direct-in-liquid Electrical Discharge Plasma in Low Conductivity Solutions

Abstract: This work investigates and reveals the main mechanism(s) responsible for inactivation of E. coli by in-liquid pulsed electrical discharge plasma in low conductivity solutions. Experiments were designed and performed to explore the effects of plasma-emitted UV light, oxidative radicals, and electric field on E. coli inactivation curves, rate of DNA leakage and visual appearance of the treated microorganisms. Results showed that electric field had the main role in inactivation; scanning electron microscopy image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 51 publications
(55 reference statements)
2
11
1
Order By: Relevance
“…Error bars represent standard error of the mean by a smaller change in pH compared to Milli-Q. Previous research has also demonstrated that in situ plasma treatment elicits physical conditions on microbes, including electric fields (Estifaee et al, 2019) and ultraviolet radiation (Zheng, 2017), that can further contribute to antimicrobial power. Further research is required to fully understand what causes the biocidal effects of BSD-PAW in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent standard error of the mean by a smaller change in pH compared to Milli-Q. Previous research has also demonstrated that in situ plasma treatment elicits physical conditions on microbes, including electric fields (Estifaee et al, 2019) and ultraviolet radiation (Zheng, 2017), that can further contribute to antimicrobial power. Further research is required to fully understand what causes the biocidal effects of BSD-PAW in situ.…”
Section: Discussionmentioning
confidence: 99%
“…Other reactive species that could not be elucidated in this study, or synergy between components of the complex mixture present in BSD-PAW, may have been responsible for its bactericidal activity. In addition, recent studies suggest that plasma treatment elicits physical conditions, including electric fields (30), that were not investigated here. Further research is required to fully understand what causes the biocidal effects of BSD-PAW.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chemical species derived from the air plasma indicates a better result compared to the chemical species from Ar plasma ( Cubas et al, 2021 ). Then, the upper electrode of the gas phase that discharges close to the water surface indicates the high damage of bacteria, followed by reactive species’ attack ( Estifaee, 2019 ). Thus, the inactivation of bacteria can be obtained by plasma technology.…”
Section: Degradation Of Contaminants In Plasma Technologymentioning
confidence: 99%